Pengaruh Penerapan Spiritual Leadership terhadap Komitmen Perawat pada Organisasi di Rumah Sakit Islam Surabaya - Asmaningrum, Nurfika; Keliat, Budi Anna; Hastono, Sutanto Priyo (Jurusan Keperawatan FIKES UNSOED, 2011)
Nurse's commitment and loyalty are important things in the health care sectors, to develop good work performance and productivity. Human resources management in Surabaya Islamic hospital that related nurse retention still focused in extrinsic efforts. In the future need comprehensive management to stimulate nurse intrinsic motivation to be more committed. Spiritual leadership is gained to develop organizational commitment based on integration of altruistic love and organizational culture. This research to investigate the influence of spiritual leadership effects on nurse’s organizational commitment in Surabaya Islamic Hospitals based on the control group with pre and post test design. The subjects are 82 nurses, divided into intervention and control group in Surabaya Islamic Hospitals nursing care wards. Instruments to examine organizational commitment is measured by using adaptations Psychological Attachment Instrument which is presented by O’Reilly dan Chatman. Data analysis used mean t-test also liniary multiple regression. The result showed that there was significant differences after practiced spiritual leadership and before practiced (p value=0.000). There was significant differences between nurse’s organizational commitment that practiced spiritual leadership and no practiced (p value=0.005). The factors used to predict increases nurses organizational commitment in research showed that spiritual leadership, female gender, married status, increases age also long nurse’s tenure. Spiritual leadership based on vision, altruistic love, hope/ faith will be stimulate spiritual survival with could to develop nurse calling and membership, and then driver organizational commitment. Sustainaibility implementation spiritual leadership must be continue and develop